Circulating primers enhance platelet function and induce resistance to antiplatelet therapy. (25th June 2015) - Blair, T. A.; Moore, S. F.; Hers, I.
Summary Background Aspirin and P2Y12 antagonists are antiplatelet compounds that are used clinically in patients with thrombosis. However, some patients are 'resistant' to antiplatelet therapy, which increases their risk of developing acute coronary syndromes. These patients often present with an underlying condition that is associated with altered levels of circulating platelet primers and platelet hyperactivity. Platelet primers cannot stimulate platelet activation, but, in combination with physiologic stimuli, significantly enhance platelet function. Objectives To explore the role of platelet primers in resistance to antiplatelet therapy, and to evaluate whether phosphoinositide 3‐kinase (PI3K) contributes to this process. Methods and Results We used platelet aggregation, thromboxane A2 production and ex vivo thrombus formation as functional readouts of platelet activity. Platelets were treated with the potent P2Y12 inhibitor AR‐C66096, aspirin, or a combination of both, in the presence or absence of the platelet primers insulin‐like growth factor‐1 (IGF‐1) and thrombopoietin (TPO), or the Gz‐coupled receptor ligand epinephrine. We found that platelet primers largely overcame the inhibitory effects of antiplatelet compounds on platelet functional responses. IGF‐1‐mediated and TPO‐mediated, but not epinephrine‐mediated, enhancements in the presence of antiplatelet drugs were blocked by the PI3K inhibitors wortmannin and LY294002. Conclusions These results demonstrate that platelet primers can contribute to antiplatelet resistance. Furthermore, our data demonstrate that there are PI3K‐dependent and PI3K‐independent mechanisms driving primer‐mediated resistance to antiplatelet therapy.